Management of Chronic Diseases through Oral Health and Nutrition Strategies - Ubbes, Valerie A; Bailey, Abram (Archives of Clinical and Biomedical Research, 2026)
The relationship between nutrition and oral health remains a vital component of overall health. According to the Academy of Nutrition and Dietetics, oral health and nutrition have a synergistic multidirectional relationship in human health. The World Health Organization promotes a global oral health action plan to reduce sugar consumption in 50 percent of countries by 2030, with the aim of reducing overweight, obesity, chronic systemic infection, and dental caries. The intersection between oral health and noncommunicable chronic diseases is important because the oral cavity has a profound impact on systemic health. With the National Institute of Health’s release of the 2021 book, Oral Health in America: Advances and Challenges, there is an ongoing need for narrative reviews to describe research connections between oral health and the prevention of cardiovascular disease, diabetes, rheumatoid arthritis, respiratory disease, gastroesophageal reflux disease, and Alzheimer’s disease. Because the microbiomes of the oral cavity, gut, and brain share access to food and nutrients, a summary of microbiota activity can be helpful for professionals when discussing dental caries and periodontitis with their patients. The purpose of this paper is twofold: 1) to review current research highlighting the relationship between chronic diseases and oral health, and 2) to outline practical oral health, nutrition, and lifestyle strategies for dentists and dietitians so they can talk about chronic disease prevention with their patients and clients.